The diagnostic algorithm patients examination with penile deformation - Arkatov, Andriy; Knigavko, Oleksandr (My University, 2016)
The article outlines informational content of the methods used for treatment and diagnostic algorithm development for patients with different types of of penile deformations. It is given retrospectively the assessment to ultrasound, X-ray, and magnetic-resonance tomography, as well as are evaluated the results of surgical treatment of patients with penile deviations. There are provided recommendations to examitaion of patients with penile deformations of different etiology.
Keywords: magnetic-resonance tomography (MRT); penile deformation; peyronie’s disease; ultrasound; diagnostic algorithm